Modelling Organic Farming at Sector Level. An Application to the Reformed CAP in Austria - Erwin Schmid; Franz Sinabell (Austrian Institute of Economic Research (WIFO), 2007)
Organic farming practices have environmental benefits compared to conventional ones. Their adoption is the result of a complex interaction of intrinsic attitudes of farmers, their profit expectations and farm policy incentives. We use an agricultural sector model and develop an extended version of the Positive Mathematical Programming (PMP) method to differentiate organic farming from other management practices. Austria is chosen for the case study because 8 percent of its farmland are managed organically, and detailed data on alternative management practices are available. The results suggest that the agricultural policy reforms have made organic farming more attractive to farmers.
Keywords: 330; Organic farming; Common Agricultural Policy; Program for Rural Development; Agricultural Sector Modelling; Ökologischer Landbau; EU-Agrarpolitik; Ländliche Entwicklung; Wirkungsanalyse; EU-Staaten